Attitudes of Primary School Teachers and Its Associated Factors Toward Students With Attention Deficit Hyperactivity Disorder in Debre Markos and Dejen Towns, Northwest Ethiopia - Amha, Haile; Azale, Telake (Frontiers in Pediatrics, 2022)
Background: Most educators seem to understand noticeable disabilities such as blindness and other disabilities. They seem to have a preconception about children with attention deficit hyperactivity disorder, believing them to be lazy or deliberately disruptive. There is a dearth of evidence about the attitude of teachers towards children with Attention deficit hyperactivity disorder in Ethiopia. Methods: An institution based cross-sectional study was conducted. A pre-tested questionnaire which contains case vignette was administered by face-to-face interview with 417 teachers who were selected by random sampling from each school. The data was entered into Epi-data version 4.2 and exported into SPSS version 25.0 for analysis. Descriptive statistics were used to describe sociodemographic factors and to assess teachers` attitude. Simple and multiple linear regression analyses were used to assess the correlates of attitude in the participants and B coefficient with 95% confidence interval were used. The statistical significance was accepted at p-value < 0.05. Results: The mean score of the teachers` attitude towards Attention deficit hyperactivity disorder was 41.6± 5.4 (95% CI; 41.12, 42.16). Less than half of the respondents 192(46%) scored below the mean score. Certificate level of education (B; -4.92, CI; -6.44, -3.39), knowledge (B;0.47, CI;0.37,0.56), duration of teaching (B;0.18, CI;0.15,0.22), experience in teaching students with attention deficit hyperactivity disorder (B; 4.27, CI; 3.27, 5.27) and training (B; 2.79, CI; 0.33, 5.24) were significant factors. Conclusion: The study revealed that participants had a lower mean score of attitude towards Attention deficit hyperactivity disorder compared to other studies. Knowledge, duration of teaching, having a training and experience in teaching students with Attention deficit hyperactivity disorder were predictors of favorable attitude whereas having a certificate level education was a predictor of unfavorable attitude. Based on the findings, it was recommended that it is better to strengthen training of teachers to recognize students with attention deficit hyperactivity disorder.